Analisis Kalimat pada Teks Cerita Sejarah dalam Buku Sosiologi Kelas XI Kurikulum Merdeka - Mukhamad Dwi Prasetyo; Muhamad Taufiq Hamdani; Yayang Vintoko; Ahmad Mirza Aufa; Asep Purwo Yudi Utomo; Yerry Mijianti (Pusat Riset dan Inovasi Nasional, 2023)
This article examines the analysis of sentence types in the History Text of Class XI Sociology Books in the Merdeka Curriculum. The content of this study uses narrative text. The purpose of this study is to describe functions, categories, and roles at the syntactic level. sentences in the presentation of sociology book material for class XI SMA/MA contained in Chapter 2 Social Problems Due to Social Grouping pages 41 to 81. This research is a literature study. Therefore, the method used in collecting data is reading and taking notes. The collected data were analyzed by descriptive analysis. In qualitative research, data is analyzed inductively, which means that specific things found during the research are grouped and conclusions are drawn from these results. This approach does not use the collected data to prove or disprove the hypotheses that have been made before but rather focuses on describing data to facilitate understanding. The writing method of this research adopts historiography as the main approach. Sentence structure analysis is also used to improve grammar skills and abilities to better understand. Sentence structure analysis itself is a topic that is rarely discussed. To improve the application of linguistic rules in writing historical texts, a good understanding of grammar, a broad vocabulary, and a habit of reading and writing historical texts are required. Therefore by analyzing sentence structures in historical texts in Sociology Class XI books SMA/SMA/ MA Kurikulum Merdeka, this research provides an overview of the variations in the use of sentence structures and the importance of correct grammar in understanding texts. It is hoped that this research can improve understanding of syntax and grammar which will facilitate understanding of sociology and historical texts.